Analysis of transfusion of blood and blood products and their utilization pattern at department of obstetrics of tertiary care hospital - Vasava, Dipti C.; Thaker, Rajal V.; Tyagi, Aditi A.; Patel, Foram P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In developing countries, nutritional anaemia and obstetric complications are leading causes of transfusion of blood and blood products. The study was aimed to analyse utilization pattern and to identify the indications of transfusion of blood and blood products in obstetrics and to study outcome and management of pregnancy in patients who required blood and/or blood products. Methods: This retrospective study was carried out at department of obstetrics of tertiary care teaching hospital from September 2018 to November 2018 and data was collected from all patients who had received transfusion of blood and/or blood products for any obstetric cause. Results: A total of 164(6.8%) patients received blood and blood products transfusion. Department of obstetrics utilized maximum units of blood and FFP whereas PRC utilization was second highest. There were 62(37.8%) of patients who had not taken any antenatal care, whereas 64(39.0%) patients had less than 4 antenatal visits. Three most common indications for transfusion of blood and blood products were 63.4% in nutritional anaemia, 17.1% in obstetric haemorrhage and 11.6% in first trimester complications. Conclusions: Three most common indications for transfusion were nutritional anaemia, obstetric haemorrhage and first trimester complications. Majority of patients had inadequate or no antenatal care. Early and regular antenatal care, early diagnosis and management of high-risk pregnancies and obstetric complications, institutional delivery can reduce the rate of transfusion of blood and blood products.